Jóźwiak Sławomir and Szweda Adam. Dwór wielkich mistrzów zakonu krzyżackiego w Malborku. Siedziba i świeckie otoczenie średniowiecznego władcy zakonnego. Toruń: Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2022: [The Court of the Grand Masters of the Teutonic Order in Marienburg. The residence and secular surroundings of a medieval monastic ruler]. - Czwojdrak, Bożena (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
375 pp. ISBN: 978-83-231-4632-2. eISBN: 978-83-231-4632-2.